2020
DOI: 10.1111/jgh.14985
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative quality of life after laparoscopy‐assisted pylorus‐preserving gastrectomy compared with laparoscopy‐assisted distal gastrectomy for early gastric cancer

Abstract: This study aimed to investigate the QOL between LAPPG and LADGBI in patients with middle-third EGC. By EORTC Questionnaire QLQ-C30 and QLQ-STO22, we found that compared to LADGBI, LAPPG obtains QOL as well as serum total protein and hemoglobin superiority for middlethird EGC. 1 Chen Huang and Fengrong Yu contributed equally to this work.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 31 publications
0
32
0
Order By: Relevance
“…PPG is a less-invasive function-preserving procedure that has been applied for the cT1N0M0 middle-third EGC with a distal tumor border at least 4 cm proximal to the pylorus according to the Japanese GC treatment guidelines [ 5 ]. The survival and recovery benefits of PPG have already been reported in several retrospective studies [ 30 32 ]. However, the performance of PPG remains controversial.…”
Section: Discussionmentioning
confidence: 92%
“…PPG is a less-invasive function-preserving procedure that has been applied for the cT1N0M0 middle-third EGC with a distal tumor border at least 4 cm proximal to the pylorus according to the Japanese GC treatment guidelines [ 5 ]. The survival and recovery benefits of PPG have already been reported in several retrospective studies [ 30 32 ]. However, the performance of PPG remains controversial.…”
Section: Discussionmentioning
confidence: 92%
“…PPG is a lessinvasive function-preserving procedure that has been applied for the cT1N0M0 middle-third EGC with a distal tumor border at least 4 cm proximal to the pylorus according to the Japanese GC treatment guidelines [3]. The survival and recovery bene ts of PPG have already been reported in several retrospective studies [22][23][24]. However, PPG remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have confirmed that the probability of suprapyloric LNM in T1 stage EGC in the middle of the stomach is only 0.2%. Therefore, lymph node dissection in the suprapyloric region can be omitted or only partially dissected to preserve the hepatic branch, the celiac branch, and the pyloric branch of the vagus nerve and the right gastric vessel, so as to seek a balance between the radical resection of the tumor and the function preservation as far as possible, and at the same time reduce the incidence of postoperative gastric emptying and improve the postoperative life quality of patients[ 59 , 60 ]. We also think that anastomotic methods might be associated with gastric emptying disorder occurrence after PPG, that is, manual suture might be better than Stapler.…”
Section: Management After Additional Surgery In Patients With Endoscopic Resectionmentioning
confidence: 99%